UPAYA PEMBERDAYAAN DAN PENINGKATAN PROMOSI UMKM DESA BAGOR, MIRI, SRAGEN MELALUI PELATIHAN FOTOGRAFI PRODUK MELALUI SMARTPHONE - Prilosadoso, Basnendar Herry; Rizkizh, Ditya Fajar; Ridlo, M. Harun Rosyid; Setiawan, William; Maharani, Utin Della; Santi, Oasis Fadila; Bagaskara, Danendra (Institut Seni Indonesia Surakarta, 2024)
Marketing via Internet media is currently commonly known as digital marketing. Digital marketing is one of the marketing media that is currently in demand by society because it can reach a wider target consumer quickly and precisely, more effectively and efficiently. In making maximum use of promotional media, the ability to create new and unique creations is needed so that messages can stick with consumers, so that the goal is to reach more consumers, one of which is photography. The partners of this PKM are UMKM in Bagor Village, Miri, Sragen, where there are around 18 products pioneered by community members. The problems faced by can be concluded based on several aspects, namely the lack of ability to promote in online media in increasing the marketing of UMKM products through online media, such as Instagram, Twitter, Facebook and other social media and UMKM members have not received basic knowledge and skills regarding product photography via camera. mobile phones as a medium for increasing sales and marketing. The solution to this problem is in the form of simple product photography training using smartphones and other supporting properties. Community empowerment is a concept of economic development in society that summarizes community values ​​to build a new way of seeing people towards themselves and their environment that is people centered, participatory, empowering and sustainable. The stages in UMKM product photography training are as follows: Mini Studio Creation and Lighting Stage; Photo Concept Preparation Stage; Stages of Product and Property Arrangement; Shooting Stages; and Photo Editing Stages. Through this training, product photos are produced which function to increase the added value of UMKM production in Bagor, Miri, Sragen Villages as well as increasing the insight and knowledge of community members in terms of promotion and marketing in the future, as well as increasing welfare. Keywords: Empowerment, Bagor Village, Training, Product Photography, Smartphone